Pengembangan Media Pembelajaran Berbasis Linktree Pada Mata Kuliah Pengantar Ilmu Kependidikan - Eka Widyawati; Nurmala R (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to develop a Linktree-based learning media for the Introduction to Education course that is valid and practical. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analyze, Design, Develop, Implement, and Evaluate stages. In the analysis phase, a need assessment was conducted to identify students’ needs for technology-based learning media. The results indicated that most students require learning media that are flexible, interactive, and accessible online. The developed product is a digital Linktree platform containing various learning features such as brainstorming, videos, materials, motivation, and quizzes. The validation results showed that the media achieved a score of 93.25% (very valid), while the material validation reached 94% (very valid). The practicality test results showed 96.3% in the small group test and 96.2% in the field test, both categorized as very practical. Therefore, the developed Linktree-based learning media is feasible to be used in the learning process.